Die Verband tussen Organisasiestruktuur en Kommunikasieklimaat - Maria Thirion; Anton Verwey (Communicare)
The aim of this study was to determine the nature of the relationship between organisational structure and communication climate. Based on a specific schedule, interviews were conducted with senior human resource managers in six organisations to obtain a of organisational structure. These organisations were chosen for their apparent differences on five structural dimensions. The communication climate within each of these organisations was then assessed by means of a questionnaire. The communicate climate patterns of the organisations were then compared by means of profile analysis. The results seem to indicate that there is indeed a relationship between organisational structure and communication climate. Specifically a more positive climate for formal communication is found with in degrees of structuring.